The first four terms of a quadratic number pattern are \( -1 ; 2 ; 9 ; 20 \) 2.1.1 Determine the general term of the quadratic number pattern.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find the general term of the quadratic pattern, we start by observing the terms: \( -1, 2, 9, 20 \). We calculate the first differences: \[ 2 - (-1) = 3, \] \[ 9 - 2 = 7, \] \[ 20 - 9 = 11. \] Now, the second differences are: \[ 7 - 3 = 4, \] \[ 11 - 7 = 4. \] Since the second differences are constant, the sequence is quadratic, taking the form \( an^2 + bn + c \). Using the first four terms, we set up the following equations: 1. For \( n=1 \): \( a(1)^2 + b(1) + c = -1 \) ⇒ \( a + b + c = -1 \) 2. For \( n=2 \): \( a(2)^2 + b(2) + c = 2 \) ⇒ \( 4a + 2b + c = 2 \) 3. For \( n=3 \): \( a(3)^2 + b(3) + c = 9 \) ⇒ \( 9a + 3b + c = 9 \) Now we have a system of three equations: 1. \( a + b + c = -1 \) (1) 2. \( 4a + 2b + c = 2 \) (2) 3. \( 9a + 3b + c = 9 \) (3) Subtract equations (1) from (2) and (2) from (3) to eliminate \( c \): From (2) - (1): \[ 3a + b = 3 \] (4) From (3) - (2): \[ 5a + b = 7 \] (5) Now, subtract equation (4) from (5): \[ (5a + b) - (3a + b) = 7 - 3 \] \[ 2a = 4 \] \[ a = 2 \] Now substitute \( a = 2 \) back into equation (4): \[ 3(2) + b = 3 \] \[ 6 + b = 3 \] \[ b = -3 \] Finally, substitute \( a \) and \( b \) into equation (1): \[ 2 - 3 + c = -1 \] \[ -1 + c = -1 \] \[ c = 0 \] Thus, the general term of the quadratic number pattern is: \[ T(n) = 2n^2 - 3n \]